Fishery, population dynamics and stock assessment of geelbek (Atractoscion aequidens), a commercially important migrant fish species off the coast of South Africa - Boyd, Danielle Winona (Department of Statistical Sciences, 2018)
Geelbek (Atractoscion aequidens) is an important fish species in South Africa's linefishery, a fishing sector defined by its fishing gear of rod and reel or handline. Distributed from Cape Point (34°21'S, 18°29'E) on the south west coast to Kosi Bay (26°51'S, 32°53'E) on the east coast, they are targeted throughout their range by the commercial linefishery, recreational anglers and small-scale fishers. The majority of geelbek are caught on the Agulhas Bank during austral summer. Due to current minimum size limits of 600 mm (total length, TL), well below the 50% size-at-maturity (950 mm TL), the majority of the catches are comprised of immature fish, making the stock vulnerable to growth overfishing. Adults (>5 years) migrate seasonally to spawn off KwaZulu-Natal and congregate in offshore shoals at night. These spawning aggregations allow fishermen to catch large numbers of fish, making geelbek also vulnerable to recruitment overfishing. This study aims to improve understanding of the fishery and population dynamics of geelbek to help inform natural resource management of the geelbek linefishery. A stock assessment of South African geelbek was undertaken to fulfil this aim. For this purpose, spatially and seasonally explicit equilibrium per-recruit and dynamic age-structured operating models were developed for geelbek to account for the dynamic in stock structure as a result of the intra-annual coastal migration and differences in the vulnerability of life history stages to varying fishing pressure along South Africa's coastline. These models were developed using statistical programming environment R. The models were parameterised and calibrated using length and catch data from the National Marine Linefish System (NMLS) and life history parameters sourced from peer-reviewed literature. Per-recruit analyses were performed to estimate current stock-specific fisheries mortality rates and the spawner biomass depletion. These estimates were used as input into the stochastic age-structured simulation model and calibrated using available commercial catch data (1987 - 2011). The stochastic operating model was used to predict the probability of stock recovery and long-term sustainability under eleven alternative fisheries management strategies. The current stock status was estimated at 9.9% (approximately 10%) of the pristine spawner biomass (SB₀) using per-recruit analysis. This was compared to the stock depletion estimates of ~5 and 7% SB₀ from prior assessments conducted in the late 1990s and 1980s. This study indicated that there was a ~50 to 100% increase in spawner biomass over the past twenty years. However, this level of stock depletion is still considered critically low with respect to the previous limit management goal of increasing spawner biomass depletion rates above 25% SB₀, the collapsed limit reference level, advised by Griffiths in 1997. Eleven management strategies were simulated, examining the effects of decreases in harvest rates, closed seasons and areas and changes in minimum size limits, initiated in 2020, and tested over the medium (ten years) to long (twenty years) term. The least efficient management strategy was continuing at the status quo, with a minimum size limit of 600 mm (TL), which predicted only 1% and 2% increase in SB by 2030 and 2040, respectively. The most efficient in terms of a rapid recovery was a full fishery closure 'control scenario' (moratorium), which predicted a recovery to the threshold reference level for sustainable fishing at 40% SB₀ by 2025, and approaching pristine levels by 2040. Increasing the minimum size limit to the size-at-50%-maturity, 950 mm TL, had the second highest recovery rate, reaching 25% SB₀ by 2027, and nearing 40% SB₀ by 2035, at which point its trajectory is asymptotic to 40% SB₀. Decreasing the harvest rate by 50% across all regions and seasons had the third highest recovery rate, reaching 25% SB₀ by 2035, but levelling off thereafter. All the other management strategies resulted in slight stock recoveries, but with all stock trajectories remaining below 14% SB₀ in the long term. Additionally, the impact of various strategies, such as increasing the minimum size limit to the size-at-50%-maturity, 950 mm TL, were unequal, with the east coast experiencing increasingly higher catches over time, whereas the catches for the south south west coast declined drastically throughout the year, and did not improve with time. Such unequal distribution of the impact of management intervention is a consequence of the migratory life history of the geelbek stock. These results provide comprehensive insights into the population dynamics and current impacts on the geelbek stock, suggesting that this species remain severely depleted at ~10% SB₀. Rebuilding the stock to sustainable levels would require serious management intervention.